Hypolipidemic and Antioxidant Properties of Phenolic Compound-Rich Extracts from White Ginseng (Panax ginseng) in Cholesterol-Fed Rabbits - Young-Chan Kim (Molecules, 2013)
In this study, the effect of low-molecular weight white ginseng compounds on various biochemical indices, including blood lipid concentrations and antioxidant enzyme activities and morphological changes was investigated in rabbits with high cholesterol diet-induced hypercholesterolemia. The experimental animals were 16-week-old male New Zealand white rabbits divided into normal control diet, high cholesterol diet, and high cholesterol with 0.05% white ginseng low-molecule compound groups, treated for 4 weeks. Blood lipid concentrations were higher in the high cholesterol groups compared to the normal control group but were not improved by the white ginseng low-molecular weight compound. We note however that antioxidant enzyme activities and morphological changes of the aorta showed that white ginseng small compounds had a positive effect on hypercholesterolemia. Based on such results, low-molecular weight compounds rich in phenolic compounds in white ginseng can be said to be effective in part in improving hyperlipidemia and atherosclerosis induced by a high cholesterol diet among New Zealand white rabbits.